Stability Indicating Analytical Method Development and Validation for the Estimation of Calcium Dobesilate in Bulk Drug Using RP-HPLC (Asian Journal of Pharmaceutics (AJP), 2024)
Introduction: The aim of the study is to develop a simple, precise, accurate, linear, and rapid stability-indicatingmethod for the separation and identification of degradation products and mass studies of calcium dobesilate (CAD)drugs used in the treatment of diabetic retinopathy and chronic kidney disease as per the International Conferenceon Harmonization’s (ICH) guidelines. Materials and Methods: The technique makes use of an isocratic mode,an Enable C18 Kromasil (250 × 4.6 mm; 5μ) column, and a reverse phase column. The optimal parameters forthe method are the mobile phase of acetonitrile (0.1%), OPA in water (20:80), a flow rate of 1 mL/min, and aUV detector with a detection wavelength of 310 nm. Results and Discussion: Degradation was carried out andCAD was sensitive to base conditions. Structure elucidation of the forced degradation products was observedusing liquid chromatography-mass spectrometry. CAD was found to be stable under thermal, photolytic, acid, andperoxide conditions. Two degradation products were reported, but we did not get the m/z of degradation productsof CAD. We report these degradation products as unknown impurities. The suggested procedure was validatedin accordance with ICH Q2 (R1) standards. Accuracy studies were observed that the percentage recovery wasfound to be 98.0–102.0% and the linearity of the method was excellent over the range of 80–120 μg/mL. Relativestandard deviations of 0.612% demonstrate the precision. The results showed that the limits of detection andquantitation were, respectively, 0.477 and 1.445 ug/mL. Conclusion: According to validation and degradationresults, the method was found to have good stability, indicating its nature as well as being user-friendly